Green financing for global energy sustainability: prospecting transformational adaptation beyond Industry 4.0. Issue 1 (1st January 2021) - Ng, Artie W.; Nathwani, Jatin; Fu, Jingyan; Zhou, Hui
Abstract: Based on a review of both interdisciplinary and policy literature pertaining to the intertwined issues of global economic recovery and sustainability, this article derives a framework of transformational adaptation organized around four objectives. First, we prospect the emergence of a green financing system to integrate international capital markets that sets priorities for climate financing and encourages progress toward the United Nations Sustainable Development Goals (SDGs) to foster energy sustainability in concert with the development of Industry 4.0 on a global scale. Second, this article articulates the imperative of embracing developing economies under a green recovery framework. Third, we point out the recent advancement in cost efficiency of clean energy technologies that rationalize financial decisions for the replacement of fossil fuels. Finally, the study reveals the clustering of green financing institutions as globally distributed hubs for redirecting investments into sustainable infrastructures consistent with the goal of mitigating climate change as advocated in the Paris Agreement. We identify the main challenges that constrain this transformational adaptation, particularly timely technology transfer of advanced clean energy technologies across the globe.